THE INTERNAL FACTORS AFFECTING LUNG CAPACITY OF PEOPLE LIVING IN AREAS AROUND THE CEMENT INDUSTRY, INDONESIA - Jayadipraja, Erwin Azizi; Daud, Anwar; Assegaf, Alimuddin Hamzah; -, Maming (YCAB Publisher & IAKMI SULTRA, 2016)
Background: Some internal factors have both positive and negative effects to people's health, especially those who live in a polluted area. The area around the cement industry is an example of polluted area in which the lung capacity will be harmed.Aim: This research aimed at finding out internal factors affecting lung capacity of people living in the area around the cement industry.Methods: This research used a cross sectional study plan by measuring lung capacity (FEV1 and FVC) of people living in four different locations. The locations were based on wind directions and within 3 km from the cement industry. The study plan was also done by connecting the measurement with other factors, such as age, physical activities, nutrition status and passive smoking or environmental tobacco smoke (ETS).Results: Based on the calculation of lung capacity 241 respondents obtained 123 respondents (51%) had a normal lung capacity, 105 respondents (43.6%) had a restricted lung capacity, 4 respondents (1.7%) had an obstructed lung capacity and 9 respondents (3.7%) had a combination of a restricted and obstructed lung capacity. The age (p=0.977) and physical activities (p=0.087) of respondents had no effect on the lung capacity. However, nutrition status (p=0.011) and passive smoking or ETS (p=0.003) do.Conclusion: The nutrition status and the presence of a passive smoker were the internal factors affecting people's lung capacity, especially for those who live around the cement industry. Thus, in order to avoid the impairment of lung capacity, people need to improve their nutrition and to avoid people smoking around them.